1999
DOI: 10.1177/03635465990270012001
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Properties and Functional Aspects of Taped Ankles

Abstract: We used electromyographic and goniometric methods to test 40 subjects to describe the neuromuscular and biomechanical adaptation of the ankle with respect to application of two different adhesive tapes and to exercises. The neuromuscular responses to inversion injury simulation, together with the mechanical displacements of the joint complex, were analyzed before and after controlled athletic exercises. The proprioceptive amplification ratio was calculated on the basis of the integrated reflex electromyographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
12

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 22 publications
2
55
0
12
Order By: Relevance
“…8,42 The mechanisms responsible may not only be due to the mechanical restriction of the range of ankle inversion. Hypotheses as to other prophylactic benefits of applying adhesive tape include deceleration of the inversion motion, 42 afferent input to the central nervous system, 15,22,33,37,42 and placebo effects. 34 In 1980, a new type of elastic tape called Kinesio Tape (KT) was introduced by Kenzo Kase.…”
Section: T T Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…8,42 The mechanisms responsible may not only be due to the mechanical restriction of the range of ankle inversion. Hypotheses as to other prophylactic benefits of applying adhesive tape include deceleration of the inversion motion, 42 afferent input to the central nervous system, 15,22,33,37,42 and placebo effects. 34 In 1980, a new type of elastic tape called Kinesio Tape (KT) was introduced by Kenzo Kase.…”
Section: T T Resultsmentioning
confidence: 99%
“…With respect to the effects of WT, our results are in agreement with those of previous studies that have shown increased muscle activity after application of nonelastic adhesive tape. 22,23 This has been thought to occur via cutaneous cues provided by the adhesive tape. However, the nonelastic versus elastic properties of the 2 types of tape may not offer identical stimuli during the dynamic trials of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rigid tape is known to lose some of its restrictive properties after exercise, and we did not evaluate the effects of either tape after exercise 30,31 . The efficacy of the KT may have been affected by the slit for the electrode.…”
Section: Discussionmentioning
confidence: 99%
“…Among these measures use of prophylactic ankle measures is common among players of sports either as a means of preventing ankle injuries or as a rehabilitation strategy. Numerous studies [14][15][16][17][18][19][20][21] have investigated the effectiveness of ankle taping and braces, with findings generally supporting the role of strapping and bracing in reducing the incidence of ankle sprain injuries. For example, the incidence rate of ankle sprains among braced soccer players was reported as 3% as compared with 11% among unbraced soccer players 12) .…”
Section: Introductionmentioning
confidence: 99%